How do rice consumers trade off sustainability and health labels? Evidence from Vietnam - Cuong, Ong Quoc; Connor, Melanie; Demont, Matty; Sander, Bjoern Ole; Nelson, Katherine (Frontiers in Sustainable Food Systems, 2022)
Introduction Strategies for increasing rice production in the Asian Mega-Deltas have led to environmental degradation, resource overexploitation, and high greenhouse gas emissions. Certified sustainable production labels can support governments in their efforts to render rice value chains more sustainable by simultaneously fostering planetary and human health. Little is known, however, about how consumers trade off sustainability and health attributes in staple crops such as rice. This study aims to fill this knowledge gap by investigating Vietnamese consumers' preferences and willingness to pay for rice characterized by multi-attribute sustainability and health certification labels. Methods We collected empirical data from 410 supermarket consumers in Can Tho, Vietnam using a choice experiment survey. The results were analyzed using a mixed logit model to determine consumers' preferences for sustainability and health traits in rice. Four price levels were used to elicit willingness-to-pay for four certification labels: low-emission, eco-friendly, ethically produced, and low glycemic index rice. By separating the components that make up the concept of sustainability and by including a label related to personal health and diet preferences, we are able to gain an understanding of the value consumers place on attributes that benefit the common good vs. attributes that benefit the individual consumer. Results The results showed that consumers were willing to pay a price premium for all certification labels, with the highest marginal utility assigned to low glycemic index rice. Discussion Certification of eco-friendly and ethical production generated similar utility levels, while low-emission rice was valued lower, although it still fetched a significant price premium compared to the status-quo option of rice with no certifications. The results of this study can help policymakers and value chain actors develop rice value chains that integrate sustainable production practices as well as foster the nutrition and health of rice consumers.